Nitrogen-limited cultivation of locally isolated Desmodesmus sp. for sequestration of CO2 from simulated cement flue gas and generation of feedstock for biofuel production. Issue 4 (August 2021) - Premaratne, Malith; Liyanaarachchi, Vinoj Chamilka; Nishshanka, Gannoru Kankanamalage Sanuji Hasara; Nimarshana, P.H.V.; Ariyadasa, Thilini U.
Abstract: Biological CO2 sequestration from flue gas using microalgae has emerged as a promising alternative to conventional carbon capture technologies, since it concurrently generates valuable biomass which can be utilized to produce biofuels. In the current study, the locally isolated microalga Desmodesmus sp. was utilized for sequestration of CO2 from gas mixtures simulating undiluted cement flue gas (1x), and cement flue gas diluted by two-fold (1/2x), four-fold (1/4x) and eight-fold (1/8x). The current study aimed to assess the feasibility of maintaining high CO2 sequestration rates in nitrogen-limited culture media while simultaneously producing biomass rich in target metabolites for biofuel production. Accordingly, Bold's Basal Medium (BBM) and BBM with three times the standard nitrate concentration (3N-BBM) were employed as culture media for nitrogen limited and nitrogen replete experiments respectively. The highest CO2 fixation rates were demonstrated in undiluted flue gas containing 15.50% CO2 . Moreover, the average CO2 fixation rate of Desmodesmus sp. over the 8-day cultivation period (0.21 ± 0.02 g/L/d) was not significantly reduced in nitrate limited media (BBM). Nitrate limited cultivation in undiluted flue gas enhanced the accumulation of carbohydrates in microalgae (32.44 ± 0.45% and 327.65 ± 23.39 mg/L), although the increment in lipid content was not as significant as expected (41.54 ± 1.13% and 419.57 ± 31.52 mg/L). Biodiesel properties of microalgal lipids were within the limits of the ASTM D6751–12 standard. Higher heating values of microalgae biomass were in the range of 21.97–23.17 MJ/kg. Nonetheless, pilot scale studies using actual flue gas are essential prior to microalgal biofuel production and simultaneous CO2 sequestration. Graphical Abstract: ga1 Highlights: Locally isolated Desmodesmus sp. was grown in various dilutions of cement flue gas. Desmodesmus sp. demonstrated maximum growth in undiluted flue gas with 15.50% CO2. Nutrient limited culture media exhibited a CO2 fixation rate of 0.21 g/L/d. Carbohydrate and lipid accumulations reached 32.44% and 41.54% respectively. Biomass composition and biofuel properties indicate applicability as biofuels.